PENGEMBANGAN MEDIA COMPACT DISC INTERAKTIF DALAM PEMBELAJARAN MEMBACA PUISI DENGAN MODEL SELF DIRECTED LEARNING UNTUK KELAS XII SMK NEGERI 14 SAMARINDA - Nurul Fadilah Fadilah (Kantor Bahasa Kalimantan Timur, 2018)
Product development of interactive compact disc media in reading poetry learning with self directed learning model for class XII of SMK Negeri 14 Samarinda is highly recommendedto be used as an innovation and improve the quality of learning. This study aims to determinethe process of developing an interactive compact disc media and reveal the quality of products in the form of validity, attractiveness and effectiveness of the use of interactive media product development compact disc in reading poetry learning with self directed learning model. This research uses Research & Development (R & D) approach. The results of this study mention the quality of products through the assessment of material experts mentioned 92%, designers oflearning mentions 92.8%, linguists mention 87.25 and media experts 1 mentions 90.6% and media expert 2 mentions 94.6%. The results of the assessment through APKG I and II with the achievementof 92 - 91.66 and 91.96 - 91.07 are in the range 75.01% - 100.00%, without revision, enter the categoryis very valid. Product attractiveness through small group trial with 88.0% percentage and large group trialwith percentage of 87,96% , entered very interesting category. The effectiveness of the product through student activity with the percentage of 85.51% enter the category very active (effective)